Smyrna 1922 : The destruction of a city - Dobkin, Marjorie Housepian, 1923-2013 (Kent : Kent State University Press, 1988)
A study of events that led up to a betrayal in the West of one of its allies during World War I, which led to the destruction by fire of Smyrna by the Turks in 1922. The book looks at the origins of festering current hostilities in Eastern Europe and the Middle East and attitudes to the West
Reprint. Previously published: London : Faber, 1972.
Includes index.
Bibliography: p. 236-243.
Keywords: Greco-Turkish War, 1921-1922 -- Atrocities; Fires -- Turkey -- Izmir; Minorities -- Turkey -- Izmir; Izmir (Turkey) -- History